The p67-phox cytosolic peptide of the respiratory burst oxidase from human neutrophils. Functional aspects. - Okamura, N (1990)
Most cases of cytosol-defective chronic granulomatous disease are due to the deficiency of a 47-kD protein (p47-phox) whose phosphorylation normally accompanies the activation of the respiratory burst oxidase. Recently, a form of chronic granulomatous disease was described in which the failure of O2- production was associated with the absence of a 67-kD polypeptide (p67-phox) from the cytosol of affected neutrophils. Using neutrophils obtained from a patient with this form of the disease, we examined the function of p67-phox in the activation of the oxidase. Our studies showed that in whole p67-phox-deficient neutrophils, p47-phox was phosphorylated in a normal fashion. In the cell-free oxidase-activating system, the ability of the p67-phox-deficient cytosol to support oxidase activation was partly restored by the addition of p47-phox-deficient cytosol; the p67-phox-deficient cytosol, however, was not complemented by cytosol inactivated with NADPH dialdehyde, an affinity label previously found to block the NADPH-binding component of the oxidase. Despite these differences, the kinetic properties of the p67-phox-deficient cytosol closely resembled those of the p47-phox-deficient cytosol. Taken together with earlier findings, these results suggest that (a) in the neutrophil cytosol, p67-phox is at least partly complexed to p47-phox; (b) it is in the form of this complex that p67-phox participates in oxidase activation; and (c) p47-phox appears to be translocated from the cytosol to the plasma membrane during oxidase activation, but complexation to p67-phox is not necessary for this translocation, nor for the accompanying extra protein phosphorylation.